2023
DOI: 10.1136/bmjopen-2022-069553
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of retrospective registration in clinical trial publications: a cross-sectional study of German trials

Abstract: ObjectiveProspective registration has been widely implemented and accepted as a best practice in clinical research, but retrospective registration is still commonly found. We assessed to what extent retrospective registration is reported transparently in journal publications and investigated factors associated with transparent reporting.DesignWe used a dataset of trials registered in ClinicalTrials.gov or Deutsches Register Klinischer Studien, with a German University Medical Center as the lead centre, complet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…First, we did not review the full text of RCTs to identify the reasons for retrospective or non-registration. However, we consider this a minor concern given that a recent study showed that only 3.5% of RCTs report the reasons for retrospective registration in the published manuscript 35 . Second, there is a risk of selection bias due to the low proportion of participants in our survey that intended to determine the reasons for non-prospective registration, as respondents and non-respondents might have different profiles.…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not review the full text of RCTs to identify the reasons for retrospective or non-registration. However, we consider this a minor concern given that a recent study showed that only 3.5% of RCTs report the reasons for retrospective registration in the published manuscript 35 . Second, there is a risk of selection bias due to the low proportion of participants in our survey that intended to determine the reasons for non-prospective registration, as respondents and non-respondents might have different profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has already dealt with the extent of prospective or retrospective registration of clinical trials [ 11 , 12 ], finding that between one half and two thirds of the trials are registered retrospectively. Two publications have also dealt with changes to start dates [ 13 , 14 ], finding that between 7 and 14% have changes to the start date.…”
Section: Introductionmentioning
confidence: 99%
“…In the data set of 1927 trials with a corresponding results publication, 956 (53.7%) were retrospectively registered. Publications in the International Committe of Medical Journal Editors (ICMJE) member journals did not have statistically significantly higher rates of both prospective registration and disclosure of retrospective registration, and publications in journals claiming to follow ICMJE recommendations showed statistically significantly lower rates compared with non–ICMJE-following journals 2 …”
mentioning
confidence: 96%
“…Publications in the International Committe of Medical Journal Editors (ICMJE) member journals did not have statistically significantly higher rates of both prospective registration and disclosure of retrospective registration, and publications in journals claiming to follow ICMJE recommendations showed statistically significantly lower rates compared with non-ICMJE-following journals. 2 The World Health Organization stated that retrospective in a short time frame from enrollment is preferable and acceptable compared with no registration at all. 3 It is important to allow for retrospective trial registration of studies that have not been prospectively registered to prevent the nonpublication of potentially valuable research for which human participants have given up their time and exposed themselves to risk.…”
mentioning
confidence: 99%